1992
DOI: 10.1080/00913367.1992.10673388
|View full text |Cite
|
Sign up to set email alerts
|

Mental Imagery and Sound Effects in Radio Commercials

Abstract: Advertising researchers have not investigated the impact of the imagery-evoking sound effects included in radio commercials on learning, feelings, and attitude formation. Results of the current study indicate that the inclusion of sound effects can increase imagery activity and that there is a relationship between degree of imaging and feelings. Further, it is found that imagery evoking sound effects can result in more favorable attitude toward the commercial and in improved recall and recognition of ad claims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 29 publications
3
50
0
1
Order By: Relevance
“…With regard to the effects of sound on mental imagery, several researchers found that the inclusion of sound effects increased mental imagery processing (Ferrington, 1994;Miller & Marks, 1992, 1997. Lee et al (2010), however, did not identify any significant sound effects.…”
Section: Processing Pictures and Soundsmentioning
confidence: 99%
“…With regard to the effects of sound on mental imagery, several researchers found that the inclusion of sound effects increased mental imagery processing (Ferrington, 1994;Miller & Marks, 1992, 1997. Lee et al (2010), however, did not identify any significant sound effects.…”
Section: Processing Pictures and Soundsmentioning
confidence: 99%
“…The contributions include examinations of, for instance, domestic appliances and exterior vehicle sounds (Fiore and Kelly, 2007;Jessen and Graakjaer, 2009;Miller and Marks, 1992), chocolate-cracking and paper-rustling sounds (Esch and Roth, 2005;Esch et al, 2006), bottleopening sounds (Fiore and Kelly, 2007;Rodero et al, 2015) and frictional sounds of handling cleaning and personal-care materials (Bolshakova, 2015;Knöferle et al, 2016). The issue of mediated versus unmediated sounds is discussed further in the last section of the paper.…”
Section: Non-musical Sound Brandingmentioning
confidence: 99%
“…associational meaning caused by the phonological structure and fluency). Non-verbal sounds, sometimes termed "sound effects" (Miller and Marks, 1992;Rodero et al, 2015), "auxiliary sounds" (Yorkston, 2010) or "environmental sounds" (Özcan and van Egmond, 2009;Rehan, 2016), refers to residual kinds of sound: non-verbal and nonmusical(ised) sounds that derive, or are presented as deriving, from the motion of physical objects.…”
Section: Research Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…But the significance power of sound goes much further. In this regard mental imaginary is a well-documented psychological construct defined as the image that comes to people's mind when processing non-visual information (Paivio, 1986;Miller & Marks, 1992;Schwartz, 1999). In other words, a mental image is the capacity "to see with the eye of mind, listen with the ear of the mind" (Kosslyn, Ganis & Thompson, 2010: 3).…”
Section: Music Brandingmentioning
confidence: 99%